Probing atmospheric electric fields in thunderstorms through radio emission from extensive air showers - Trinh, T. N.G.; Schellart, P.; Buitink, S.; Corstanje, A.; Enriquez, J. E.; Falcke, H.; Hörandel, Jörg R.; Nelles, Anna; Rachen, J. P.; Rossetto, L.; Scholten, O.; Ter Veen, S.; et al. (Proceedings of Science, 2015)
We present measurements of radio emission from extensive air showers taking place during thunderstorms. Their intensity and polarization patterns are different from those observed during fair-weather conditions. We introduce a simple two-layer model for atmospheric electric fields which can reproduce the main features of the intensity and polarization patterns of air shower during thunderstorms. This in turn provides a unique way to probe atmospheric electric fields.
CRIS-Team Scopus Importer:2023-08-15